Cellular impact and selectivity of half-sandwich organorhodium(III) anticancer complexes and their organoiridium(III) and trichloridorhodium(III) counterparts - Geldmacher, Yvonne; Kitanovic, Igor; Alborzinia, Hamed; Can, Suzan; Wölfl, Stefan (Journal of biological inorganic chemistry, 2012)
Half-sandwich organorhodium(III) complexes and their trichloridorhodium(III) counterparts are potent anticancer agents that enhance the formation of reactive oxygen species and invoke a strong induction of apoptosis in leukemia cells. The antiproliferative activity towards human MCF-7 and HT-29 adenocarcinoma cells of novel nonintercalating complexes containing the 5-substituted phenanthroline ligands 5,6-dimethylphenanthroline, 5-chlorophenanthroline, and 5-nitrophenanthroline (phen*) increases dramatically in the order [(η5-C5Me5)IrCl(phen*)](CF3SO3) < [(η5-C5Me5)RhCl(phen*)](CF3SO3) < mer-[RhCl3(DMSO)(phen*)] (DMSO is dimethyl sulfoxide) . Improved activity was also achieved by attaching a cell-penetrating peptide to the dipyrido[3,2-a:2′,3′-c]phenazine (dppz) ligand of an organorhodium(III) complex. Whereas 5-substitution led to significant improvements in the activity of the organoiridium(III) and trichloridorhodium(III) compounds in comparison with the parent phenanthroline complex, the IC50 values of their organorhodium(III) counterparts remained effectively invariable. The high activities of the trichloridorhodium(III) complexes (IC50 = 0.06-0.13 μM) were accompanied by pronounced selectivity towards human cancer cells in comparison with immortalized HEK-293 cells. In contrast, [(η5-C5Me5)RhCl(5,6-Me2phen)](CF3SO3) (phen is phenanthroline) was markedly more active towards BJAB lymphoma cells than ex vivo healthy leukocytes and caused an immediate decrease in cellular adhesion possibly associated with interactions with membrane proteins. Its dppz analogue invoked an initial increase in glycolysis to compensate for reduced respiration before inducing a delayed onset of cell death. Strong antimitochondrial activity with respiration impairment and release of cytochrome c was established for both complexes.